Monitoring Spatiotemporal Evolution of Urban Heat Island Effect and Its Dynamic Response to Land Use/Land Cover Transition in 1987–2016 in Wuhan, China - Qijiao Xie; Qi Sun; Zhonglu Ouyang (Applied Sciences, 2020)
Monitoring the relationship between the urban heat island (UHI) effect and land use/land cover (LULC) is of great significance in land use planning to adapt to climate change. However, the dynamic response of the UHI effect to LULC change over space and time has not been deeply studied. In this study, a transfer matrix method was carried out to monitor the class-to-class transitions between different LULC types, as well as those between different NLST (normalized land surface temperature) levels over space and time. The spatiotemporal correlation and dynamic coupling between UHI variation and LULC change from 1987 to 2016 were simulated based on multi-temporal remote sensing data in Wuhan, China. The results showed that high temperature (level V) and sub-high temperature (level IV) were mainly concentrated in construction land, while the majority of low temperature (level I) was distributed in water bodies. During the study period, the most notable changes were the rapid increase in construction land, as well as the continuous shrinkage of farmland and water bodies. The inward transfer of construction land was mainly from farmland and water bodies, with the transferred area of 218.3 km2 (69.2%) and 78.9 km2 (25.0%). These transitions were mainly responsible for the thermal deterioration in the study area. The transition of farmland to construction land contributed the most (66.3% and 81.6%) to thermal deterioration in the original medium temperature area (level III). The transition of water bodies to construction land was the main driving force in rapidly upgrading NLST level I into level IV (55.8%) and level V (58.6%). These findings provided detailed information for decision support in optimizing land use structure to fight against the thermal deterioration caused by urbanization.